As "Vidas" Profissionais do Engenheiro de Minas da FEUP - Joaquim Góis (2016)
The Professional Lives of the Mine Engineer at FEUP. Communication presented at the auditorium of the Faculty of Engineering of the University of Porto, on Santa Bárbara Day (December 5, 2016) organized by the Department of Mining Engineering